(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Cloud computing is the dynamic delivery of information technology resources and capabilities as a service over the Internet. Cloud computing is a style of computing in which dynamically scalable and often virtualized resources are provided as a service over the Internet. It generally incorporates infrastructure as a service (IaaS), platform as a service (PaaS), and software as a service (SaaS). [1] Load balancing is one of the biggest challenges in the cloud computing. The concept of load balancing is to equally distribute the workload, resources across all the nodes to guarantee that all the nodes have equal load i.e. no single node is over loaded. As we all know that cloud computing services are mainly product based so in this approach we are using different product based priority queues for different services.